Kontribusi Metode Treasure Hunt Game dan Kreatifitas Guru Terhadap Hasil Belajar Siswa dalam Pembelajaran Tematik Terpadu di Sekolah Dasar - Kessy Yolanda Resti; Desyandri Desyandri (Universitas Negeri Padang, 2021)
This study aims at finding out the contribution of the Treasure Hunt Game method and teacher’s creativity to the students’ learning outcomes in the integrated thematic learning at third-grade of elementary schools of Gugus V in Bayang District, West Sumatra. This study used a quantitative approach with a correlation design. The data were the scores of the teacher’s creativity and student’s learning outcomes in the cognitive domain in the form of objective questions. The results indicate the relationship between the teacher’s creativity and the Treasure Hunt Game method on the third-grade elementary school students’ learning outcomes. The scores of the teachers’ creativity at the first to fourth meetings were 60%, 75%, 80%, and 85%, respectively; while the average learning outcomes of the students were 66.6, 75.6, 82.2, and 87.2, respectively. At Class III of SDN 31 Ambacang, the scores of the teachers’ creativity in using the Treasure Hunt Game method at the first to fourth meetings were 65%, 75%, 85%, and 90%, respectively; while the average learning outcomes of the students at Class III of SDN 29 Ambacang were 74.4, 80, 83.3, and 86.6, respectively